Pendampingan Penerbitan Nomer Induk Berusaha (NIB) Untuk Usaha Mikro: Langkah Menuju Penguatan Ekonomi Untuk Kesuskesan Bisnis - Agung Yuliyanto Nugroho (PT. Altaf Publishing Corp, 2024)
This service aims to evaluate the effectiveness of the socialization of the Business Identification Number (NIB) among micro-entrepreneurs in Indonesia. NIB, as part of the government's efforts to simplify administration and improve legal compliance of business actors, has a crucial role in the development of the micro-business sector. However, many micro-entrepreneurs still do not fully understand the benefits and procedures related to NIB. This research method involves surveys and in-depth interviews with micro-entrepreneurs in several regions to identify their level of understanding of NIB and the obstacles they face in the registration process. In addition, documentation analysis of various socialization programs that have been carried out by government agencies was also carried out. The results of the study indicate that despite significant socialization efforts, there are still gaps in the understanding and implementation of NIB among micro-entrepreneurs. The main obstacles include lack of clear information, complexity of procedures, and limited access to socialization facilities